Efeito de diferentes tecnologias de educação em diabetes no comportamento alimentar de adolescente com DM1: um estudo de caso - ULIANA, Gabriela Correia (2023)
Introduction: Diabetes mellitus type 1 (DM1) is a genetic disease characterized by autoimmune destruction of pancreatic beta cells, resulting in the absence of insulin production. Thus, the treatment of DM1 has four axes, represented by measurement of blood glucose, insulin application, diet and physical activity. Objective: To analyze the effects of different diabetes education technologies on eating behavior of an adolescent with type 1 diabetes mellitus. Methodology: This is a case study using the longitudinally designed experimental method. The study was conducted with a 17yearold male patient, who was treated at the Endocrinology Service of a Hospital linked to the Federal University of Pará and diagnosed with DM1 for 8 years. Data were collected through the Family Support Treatment Inventory; Interview script about treatment routine; Diabetes Knowledge Scale (DKN-A); 24-hour recall (R24h); Diabetes Education Tutorial; Glic Application and Mobile Application Evaluation Protocol (Glic). Results: The patient reported selfinsulin, blood glucose alone, no diet and physical activity. She had 66.5% of family support for treatment. The usual meals were three meals a day, with low consumption of fruits and vegetables. The participant used the Glic application, however, did not make some indications proposed in the study. Regarding the DKN-A Scale, in all stages there was over 50% of the score. Conclusion: It is indicated to have nutritional monitoring to raise awareness of the importance of food in the treatment and control of diabetes, as well as multiprofessional participation to answer questions about the disease, helping the general understanding of the participant.